Molecular Pathways and Roles for Vitamin K2-7 as a Health-Beneficial Nutraceutical: Challenges and Opportunities - Jadhav, Nikita; Ajgaonkar, Saiprasad; Saha, Praful; Gurav, Pranay; Pandey, Amitkumar; Basudkar, Vivek; Gada, Yash; Panda, Sangita; Jadhav, Shashank; Mehta, Dilip; Nair, Sujit (Frontiers in Pharmacology, 2022)
Vitamin K2-7 (menaquinone-7) is a form of vitamin K that has health-beneficial effects in osteoporosis, cardiovascular disease, inflammation, cancer, Alzheimer’s disease, diabetes and peripheral neuropathy. Compared to vitamin K1 (phylloquinone), K2-7 is absorbed more readily and is more bioavailable. Clinical studies conducted by our research group have unequivocally demonstrated the utility of supplementation of K2-7 in ameliorating peripheral neuropathy, reducing the risk of bone fractures and improving cardiovascular health. We examine how undercarboxylated osteocalcin (ucOC) and matrix Gla protein (ucMGP) are converted to carboxylated forms (cOC and cMGP respectively) by K2-7 acting as a cofactor, thus facilitating the deposition of calcium in bones and preventing vascular calcification. K2-7 is beneficial in managing bone loss because it upregulates osteoprotegerin which is a decoy receptor for RANK ligand (RANKL) thus inhibiting bone resorption. We also review the evidence for the health-beneficial effects of K2-7 in diabetes, peripheral neuropathy and Alzheimer’s disease. In addition, we discuss the K2-7-mediated suppression of cancer cell growth via cell-cycle arrest, apoptosis and autophagy. The mechanistic basis for the disease-modulating effects of K2-7 is mediated through various signal transduction pathways such as PI3K/AKT, MAP Kinase, JAK/STAT, NF-κB, etc. Interestingly, K2-7 is also responsible for suppression of proinflammatory mediators like TNF-α, IL-1α, and IL-1β. We elucidate various genes modulated by K2-7 as well as the clinical pharmacometrics of vitamin K2-7 including K2-7-mediated pharmacokinetics/pharmacodynamics (PK/PD). Further, we discuss the current status of clinical trials on K2-7 that shed light on dosing strategies for maximum health benefits. Taken together, this is a synthetic review that delineates the health-beneficial effects of K2-7 in a clinical setting, highlights the molecular basis for these effects, and underscores the need for supplementation of K2-7 in the global diet.